Transducing chemical energy through catalysis by an artificial molecular motor - Peng-Lai Wang; Stefan Borsley; Martin J. Power; Alessandro Cavasso; Nicolas Giuseppone; David A. Leigh (Nature, 2025)
Abstract Cells display a range of mechanical activities generated by motor proteins powered through catalysis 1 . This raises the fundamental question of how the acceleration of a chemical reaction can enable the energy released from that reaction to be transduced (and, consequently, work to be done) by a molecular catalyst 2–7 . Here we demonstrate the molecular-level transduction of chemical energy to mechanical force 8 in the form of the powered contraction and powered re-expansion of a cross-linked polymer gel driven by the directional rotation of artificial catalysis-driven 9 molecular motors. Continuous 360° rotation of the rotor about the stator of the catalysis-driven motor-molecules incorporated in the polymeric framework of the gel twists the polymer chains of the cross-linked network around one another. This progressively increases writhe and tightens entanglements, causing a macroscopic contraction of the gel to approximately 70% of its original volume. The subsequent addition of the opposite enantiomer fuelling system powers the rotation of the motor-molecules in the reverse direction, unwinding the entanglements and causing the gel to re-expand. Continued powered twisting of the strands in the new direction causes the gel to re-contract. In addition to actuation, motor-molecule rotation in the gel produces other chemical and physical outcomes, including changes in the Young modulus and storage modulus—the latter is proportional to the increase in strand crossings resulting from motor rotation. The experimental demonstration of work against a load by a synthetic organocatalyst, and its mechanism of energy transduction 6 , informs both the debate 3,5,7 surrounding the mechanism of force generation by biological motors and the design principles 6,10–14 for artificial molecular nanotechnology.